The use of lentiviral vectors and Cre/loxP to investigate the function of genes in complex behaviors - Heldt, Scott; Ressler, Kerry (Frontiers in Molecular Neuroscience, 2009)
The use of conventional knockout (KO) technologies has proved valuable for understanding the role of key genes and proteins in development, disease states, and complex behaviors. However, these strategies are limited in that they produce broad changes in gene function throughout the neuroaxis and do little to identify the effects of such changes on neural circuits thought to be involved in distinct functions. Because the molecular functions of genes often depend on the specific neuronal circuit in which they are expressed, restricting gene manipulation to specific brain regions and times may be more useful for understanding gene functions. Conditional gene manipulation strategies offer a powerful alternative. In this report we briefly describe two conditional gene strategies that are increasingly being used to investigate the role of genes in behavior - the Cre/loxP recombination system and lentiviral vectors. Next, we summarize a number of recent experiments which have used these techniques to investigate behavior after spatial and/or temporal and gene manipulation. These conditional gene targeting strategies provide useful tools to study the endogenous mechanisms underlying complex behaviors and to model disease states resulting from aberrant gene expression.